2011
DOI: 10.1016/j.nlm.2011.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-related amnesia and dementia: Animal models have revealed the contributions of different etiological factors on neuropathology, neurochemical dysfunction and cognitive impairment

Abstract: Chronic alcoholism is associated with impaired cognitive functioning. Over 75% of autopsied chronic alcoholics have significant brain damage and over 50% of detoxified alcoholics display some degree of learning and memory impairment. However, the relative contributions of different etiological factors to the development of alcohol-related neuropathology and cognitive impairment are questioned. One reason for this quandary is that both alcohol toxicity and thiamine deficiency result in brain damage and cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 176 publications
(255 reference statements)
2
87
0
5
Order By: Relevance
“…In addition to the overall health problems caused by alcohol abuse, alcoholism is also known to cause cognitive impairments (Ryan and Butters 1983;see Stavro et al 2013 for a meta-analysis) with over 50% of alcoholics reporting memory and cognition problems (Vetreno et al 2011). The results from laboratory animal studies also demonstrate alcohol's impairing effects on cognition.…”
Section: Alcoholmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the overall health problems caused by alcohol abuse, alcoholism is also known to cause cognitive impairments (Ryan and Butters 1983;see Stavro et al 2013 for a meta-analysis) with over 50% of alcoholics reporting memory and cognition problems (Vetreno et al 2011). The results from laboratory animal studies also demonstrate alcohol's impairing effects on cognition.…”
Section: Alcoholmentioning
confidence: 99%
“…Evidence from human studies seems to be in agreement with animal studies showing chronic ethanol-induced cognitive impairments and disrupted hippocampal function. For example, impairments in learning and memory (Ryan and Butters 1983;Vetreno et al 2011), attention and executive function (Loeber et al 2009), and abstraction (Klisz and Parsons 1977; for review, see Bates et al 2002) were reported after chronic alcohol use. These cognitive deficits also persisted during abstinence (Fein et al 1990;Stavro et al 2013).…”
Section: Effects Of Prolonged Alcohol Exposure On Hippocampal Functionmentioning
confidence: 99%
“…The literature data show that in neurodegenerative pathologies (Wernicke-Korsakov syndrome, Alzheimer's and Parkinson's disease, etc. ), as well as in TD, changes in different brain regions do not occur synchronously [22][23][24]. Taking into account these observations, we conside red it worthwhile to study changes in ThDP metabolism in different parts of the brain during the Hv-T development.…”
Section: Bmentioning
confidence: 93%
“…Aunque la mayoría de las personas alcohólicas tienen trastornos cognitivos (de memoria y aprendizaje) aún se debate el papel de la toxicidad del alcohol y de la deficiencia de tiamina en estos problemas, en particular en la demencia relacionada con alcohol y en el síndrome de Wernicke-Korsakoff. En este sentido, los modelos animales muestran que los problemas relacionados con alcohol pueden ser parcialmente reversibles pero no los debidos a deficiencia de tiamina 72,73 . No hay evidencias de que el consumo ligero o moderado aumente el riesgo de demencia e incluso es posible que lo disminuya [74][75][76][77] .…”
Section: Trastornos Neurológicosunclassified